(untitled) (Interfaces: A Journal of Medieval European Literatures, 2019)
Occitan, now a regional language of France, has long been recognized as one of the most important vernaculars of the Medieval West – both for being the language of the troubadours and for being the first Romance (or Neo-Latin) language to develop a fully-fledged scripta. This article argues that unlike other regions, twelfth-century Occitania had not diglossia (learned Latin/vernacular) but triglossia. A courtly sociolect, written and spoken, vied with and even outdid Latin in large sectors of cultural production. Under particular circumstances, courtly culture, including courtly love, developed into a political and economic code whose relevance went far beyond the stylization of elite sociability with which French or German courtliness is often associated. The political culture which developed in Languedoc was one of the factors why the Albigensian Crusade (1209–29) was an unusually violent and consequential period of warfare.